Optimized Stochastic Optical Reconstruction Microscopy for Imaging Chromatin Structure in Pathological Tissue. Issue 1 (6th August 2020) - Xu, Jianquan; Ma, Hongqiang; Liu, Yang
Abstract: Direct visualization of higher‐order chromatin structure at the molecular scale is of great importance for understanding the impact of chromatin organization on gene expression in many biological processes. Understanding the changes in chromatin structure during pathological processes requires the use of in vivo models and clinical samples, and formalin‐fixed, paraffin‐embedded (FFPE) tissue is the most widespread form of preservation. Here we describe the details of PathSTORM, an optimized stochastic optical reconstruction microscopy (STORM) protocol for high‐quality super‐resolution imaging of densely packed higher‐order chromatin organization in pathological tissue. We discuss detailed methods for fluorescence staining of DNA and histone proteins, as well as the key technical factors for obtaining high‐quality STORM images in pathological tissue samples. © 2020 Wiley Periodicals LLC Basic Protocol 1 : Fluorescence staining of chromatin in pathological tissue Basic Protocol 2 : STORM data processing Support Protocol 1 : Drift correction Support Protocol 2 : Image reconstruction Support Protocol 3 : Hematoxylin & eosin (H&E) staining